Shopeefood Application During Covid-19 For Promotion And Service Quality On Consumer Purchase Decisions - Chevy Herli Sumerli A; Ana Faizah; Rusydi Fauzan; Edhie Budi Setiawan; Zaenal abidin (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
Global advances result in fierce rivalry. Customers are acquired and retained via many means. Good service quality is one of the techniques employed by businesses to win the competition. Customers are interested in purchasing a product or service due of the high level of service. This study was carried out at Bandung Islamic University to assess the impact of price, promotion, and service quality on consumer purchasing decisions for the ShopeeFood application during the Covid19 period. This study's sample included 69 students from Bandung Islamic University, and the data collected was analysed using confirmatory factor analysis (CFA) techniques. According to the study results, ShopeeFood  is still the top option for Bandung Islamic University students in terms of price, promotions, and service quality. This promotion is the major goal of students who rely on ShopeeFood to survive. Furthermore, one of the good benefits received by Bandung Islamic University students is the quality of service for drivers. Entrepreneurs are encouraged to offer competitive costs, focus on user advantages, and improve service.